Breast Health Disparities: A Primer for Medical Students - Iveris L. Martinez; Kumar Ilangovan; Ebony B. Whisenant; Maryse Pedoussaut; Onelia G. Lage (MedEdPORTAL, 2016)
Abstract Introduction While breast cancer incidence rates have remained stable and mortality rates have declined for white women, breast cancer mortality has steadily increased for African American women since the 1950s. It has often been assumed that genetic risks linked to African ancestry are the cause for these disparities. However, a better understanding of the role of stress and social and environmental factors in health lends evidence to the social determinants behind the increasing gaps in breast health outcomes. This resource's goal is to raise awareness among undergraduate medical students about breast cancer disparities, particularly the late-stage diagnoses and the higher mortality rate for African American women. Methods Our educational session included a lecture on basic epidemiological data and information on breast cancer etiology followed by a case study, which was created with the founder of a local cancer support and resource center serving mainly African American women diagnosed with breast cancer. As part of the case exercise, we utilized concept mapping as a tool to apply learning. Results Pre-/postquizzes showed significant improvements in knowledge and confidence in working with patients. Narrative reflections from students indicated an improvement in targeting at-risk populations, educating patients about their risk and options, and understanding the complex role that socioeconomic factors may play in patient outcomes. Discussion By raising awareness and exposing medical students to the socioeconomic and cultural aspects of breast health, we hope to improve medical students' knowledge of risk factors and preventive strategies, as well as their abilities to guide patients through appropriate screening and follow-up.